Tri Pusat Pendidikan Sebagai Pembinaan Akhlak Di Sekolah Dasar Negeri - Nur Afni Fauziah; Yunus Salik (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The study describes the concept of harmonization of three educational centers in moral development at UPT SD Negeri 230 Tondok Tangnga, Tanalili District, North Luwu Regency. This research is a qualitative research that uses a pedagogical approach. Sources of data, namely primary data sourced from school principals, PAI teachers, parents of students, the community. Meanwhile, secondary data were taken from documents related to the research. The instrument used in collecting data is the researcher himself who functions to determine and select informants as data sources, analyze data, interpret data, and the instruments in collecting data are observation, interviews, and documentation. The results showed that the role of the family as the basis of education, the school as the developer of education and the community as the user. An important role in the development and growth of students, both physically and spiritually, mentally spiritually and physically. The implementation of the harmonization of the Three Education Centers is carried out with close cooperation, it can be seen when parents lay the foundations of education, especially the family in the formation of personality. Then it is developed in a school environment with educational materials in the form of knowledge and skills. The community participates in controlling, distributing and fostering and improving it.